2020
DOI: 10.1021/acsami.0c15491
|View full text |Cite
|
Sign up to set email alerts
|

Highly Aligned Carbon Nanowire Array by E-Field Directed Assembly of PAN-Containing Block Copolymers

Abstract: Nanoscale engineering of carbon materials is immensely demanded in various scientific areas. We present highly ordered nitrogendoped carbon nanowire arrays via block copolymer (BCP) self-assembly under an electric field. Large dielectric constant difference between distinct polymer blocks offers rapid alignment of PMMA-b-PAN self-assembled nanodomains under an electric field. Lithographic patterning of the graphene electrode as well as straightforward thermal carbonization of the PAN block creates well-aligned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In addition, because of the growing concerns for environmental pollution and epidemics, novel sensing mechanisms are demanded to detect the hidden symptoms in a living system. Accordingly, various sensing systems are under active investigations nowadays to effectively monitor biomolecules, toxic chemicals, pollutants, ,, and other external environments (e.g., temperature and humidity). For the realization of such high-performance sensors, nanomaterials can be useful because of their inborn large surface-to-volume ratio and high surface activity clearly differentiated from bulk type counterparts. , A high surface-to-volume ratio is particularly significant, since most sensor systems rely on the surface reactions in their sensing mechanisms …”
Section: Block Copolymer Nanopatterning For Nonsemiconductor Applicat...mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, because of the growing concerns for environmental pollution and epidemics, novel sensing mechanisms are demanded to detect the hidden symptoms in a living system. Accordingly, various sensing systems are under active investigations nowadays to effectively monitor biomolecules, toxic chemicals, pollutants, ,, and other external environments (e.g., temperature and humidity). For the realization of such high-performance sensors, nanomaterials can be useful because of their inborn large surface-to-volume ratio and high surface activity clearly differentiated from bulk type counterparts. , A high surface-to-volume ratio is particularly significant, since most sensor systems rely on the surface reactions in their sensing mechanisms …”
Section: Block Copolymer Nanopatterning For Nonsemiconductor Applicat...mentioning
confidence: 99%
“…Furthermore, the conductive nanochannels created by BCP nanopatterning can be used for gas sensors. Recently, Han et al demonstrated NO 2 gas sensors by exploiting N-doped carbon nanowire arrays prepared from the direct carbonization of self-assembled BCP nanopatterns . Wei et al showed NH 3 gas sensors using electroconductive poly­(3-hexylthiophene) (P3HT) nanowire arrays produced from the self-assembly of P3HT containing BCPs .…”
Section: Block Copolymer Nanopatterning For Nonsemiconductor Applicat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the electric field assist is viable to regulate the morphology of polymers, and has often been applied to control the structural parameters of the nanostructured block copolymers on both mesoscopic and nanoscopic length scales. Tashiro et al found that the assisted electric filed (>±15 MV/m) applied to the poly­(vinylidene fluoride) (PVDF) leads to the transformation from β low‑E phase into the β high‑E phase . Sugita et al reported that the poly­( l -lactic acid) (PLLA) forms at the edge of the anode under the assisted electric field and grows in the direction parallel to the electric field, which is important to enhance the mechanical and thermal properties .…”
Section: Introductionmentioning
confidence: 99%